Modeling perception in time pedestrian space on the basis of prototypes - Buravchenko, Serhii (Theory and practice of design, 2022)
Problem statement. The organization of the perception of architectural objects in time as certain scenarios is one of the areas that allows you to attach the level of emotional expressiveness and information level of architecture to other contemporary arts, using their methods. The purpose of this article is to determine and substantiate scenario models of pedestrian space organization based on the study of established forms of various arts that unfold over time, as well as on the basis of research on the evolution and experience of forming such compositions in urban planning. The research methodology is based on the dissemination of established methods of formalizing scripts in theatrical scenography, music and cinema into architectural compositions, as well as the establishment of architectural prototypes of various script models. The results of the study cover the definition of architecturally significant scenario approaches and forms of deployment in time of different arts. The classification of the scenario models characteristic of practice of architecture and town-planning of various historical periods and concepts of formation of expressive construction of pedestrian space is developed. Historical prototypes of space models have been identified (medieval, classical, based on the dominance of natural objects and objects of the design environment, on the creation of humanized buildings). Models may have modifications in modern architecture. The practical significance of the identified models is that the architect, taking into account the current design situation, can use different methods to achieve the architectural diversity of the pedestrian space